A practical study of women’s personal growth in conditions of ambiguous loss - PARINOV, Matvii (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. The issue of ambiguous loss becomes highly relevant during wartime, when there is a need to provide qualified assistance to victims who have lost a loved one. Therefore, it is essential today to study the phenomenon of ambiguous loss, how people cope with this type of trauma, and the features of emotional reactions and recovery. Currently, in the field of psychological research, there is a gap in understanding the potential for positive personal changes resulting from ambiguous loss. Doubts about this arise because such loss is accompanied by uncertainty and a duel of emotional reactions - hope and grief. This gap creates difficulties for practical psychologists in providing adequate support. The purpose of this article was to explore the possibility and potential for personal growth in individuals experiencing ambiguous loss due to a loved one’s disappearance. Methods. To assess the potential for personal growth, a sample of 30 women, aged 19 to 60, was selected for study. The level of development was measured using the post-traumatic growth questionnaire developed by L. Calhoun and R. Tedeschi. Results. The empirical findings confirmed the possibility of personal growth in women who face uncertainty following the ambiguous loss of a loved one. The highest levels of growth were observed in the domains of "Appreciation of Life" (11.2 out of 15 points, 74.6%), "Spiritual Growth" (5.7 out of 10, 57%), and "Personal Strength" (10.5 out of 20 possible, 52.5%). The results for the domain "Improved Relationships" revealed noteworthy findings, with respondents averaging 14.3 points out of 30 (40.8%). Conclusions. The study identified the potential for personal growth in individuals dealing with loss complicated by uncertainty about the fate of the missing person. Changes in average growth rates varied depending on the availability of education, the time since receiving news of disappearance, and the kinship level. These findings offer valuable insights into the nature and impact of ambiguous loss, as well as how uncertainty influences the process of growth.